2024
DOI: 10.1002/adma.202313028
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Modulate the Copper Oxidation State Toward Selective C2+ Production in the Electrochemical CO2 Reduction Reaction

Minki Jun,
Joyjit Kundu,
Duck Hyun Kim
et al.

Abstract: The electrochemical reduction of CO2 to form value‐added chemicals has received considerable attention in recent years. Copper (Cu) has been recognized as the only element capable of electro‐reducing CO2 into hydrocarbons with two or more carbon atoms (C2+), but the low product selectivity of the Cu‐based catalyst remains a major technological challenge to overcome. Therefore, identification of the structural features of Cu‐based catalysts is of great importance for the highly selective production of C2+ produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 102 publications
0
0
0
Order By: Relevance
“…Among various screening tests involving different electrodes and electrolytes (Figure S1), two electrodes, Zn/Cu and Zn/CuZn, were selected and tested at applied potentials in 0.1 M KHCO 3 and 0.1 M K 2 CO 3 electrolytes. The reduction products were categorized into several groups: C 1 gaseous products (CO and CH 4 ), C 2 gaseous products (C 2 H 4 and C 2 H 6 ), C 3,4 hydrocarbons, major C 1 /C 2 /C 3 liquid products (formate, ethanol, and propanol), and minor C 1 /C 2 /C 3 liquid products (methanol, acetate, acetaldehyde, and isopropanol). In discussing the reduction products over Zn/Cu and Zn/CuZn electrodes, it was observed that bare Zn produced only H 2 , CO, and formate, with negligible amounts of C 2+ products . In contrast, bare Cu exhibited high FEs for C 2+ products (Figure S1), although propanol production was negligible under the present conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among various screening tests involving different electrodes and electrolytes (Figure S1), two electrodes, Zn/Cu and Zn/CuZn, were selected and tested at applied potentials in 0.1 M KHCO 3 and 0.1 M K 2 CO 3 electrolytes. The reduction products were categorized into several groups: C 1 gaseous products (CO and CH 4 ), C 2 gaseous products (C 2 H 4 and C 2 H 6 ), C 3,4 hydrocarbons, major C 1 /C 2 /C 3 liquid products (formate, ethanol, and propanol), and minor C 1 /C 2 /C 3 liquid products (methanol, acetate, acetaldehyde, and isopropanol). In discussing the reduction products over Zn/Cu and Zn/CuZn electrodes, it was observed that bare Zn produced only H 2 , CO, and formate, with negligible amounts of C 2+ products . In contrast, bare Cu exhibited high FEs for C 2+ products (Figure S1), although propanol production was negligible under the present conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The EC CO 2 reduction mechanism was inferred from the identified reduction products and established mechanistic frameworks. As mentioned earlier, the reduction products were categorized into several groups: C 1 gaseous products (CO and CH 4 ), C 2 gaseous products (C 2 H 4 and C 2 H 6 ), C 3,4 hydrocarbons, major C 1 /C 2 /C 3 liquid products (formate, ethanol, and propanol), and minor C 1 /C 2 /C 3 liquid products (methanol, acetate, acetaldehyde, and isopropanol). Additionally, H 2 emerged as a dominant product in the EC process. The production of H 2 is a well-known and common outcome, typically proceeding via the reaction H + + e – → H*, followed by association reactions such as H* + H + + e – → H 2 and H* + H* → H 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, *COOH, *CO). 9 In general, non-Cu metals exhibit poor eCO 2 RR activity towards deeply reduced products due to either strong ( e.g. H 2 mainly produced on iron, cobalt, nickel) or weak ( e.g.…”
Section: Introductionmentioning
confidence: 99%